Discourse and Dominion in the Fourteenth Century : Oral Contexts of Writing in Philosophy, Politics, and Poetry - Gellrich, Jesse M. (Book collections on Project MUSE., 2001)
This wide-ranging study of language and cultural change in fourteenth-century England argues that the influence of oral tradition is much more important to the advance of literacy than previously supposed. In contrast to the view of orality and literacy as opposing forces, the book maintains that the power of language consists in displacement, the capacity of one channel of language to take the place of the other, to make the source disappear into the copy. Appreciating the interplay between oral and written language makes possible for the first time a way of understanding the high literate ac.